1977
DOI: 10.1007/bf00717597
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for a specific transport of D-hexoses across the human term placenta in vitro

Abstract: Isolated cotylidons of human term placentas are perfused artificially on the fetal and maternal side. The relative transfer rates of radioactive labelled D-glucose, L-glucose, D-mannose and D-mannitol across the placenta are measured and the inhibition of these transports by phloretin is studied: 1. Transfer rates of D-glucose and D-mannose exceed that of L-glucose about 1.5-4 times. 2. Phloretin (10(-3) mol/l) decreases the transports of D-hexoses, whereas the transport of L-GLUCOSE REMAINS UNAFFECTED. 3. If … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
8
0

Year Published

1980
1980
2000
2000

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(10 citation statements)
references
References 10 publications
2
8
0
Order By: Relevance
“…However, given the small size of these vesicles, uptake measured at 15 sec would probably no longer be linear (Hopfer, 1978) so that uptake of D-glucose at the initial rate most likely exceeds that of L-glucose to a much greater extent. These same authors (Carstensen et al, 1977) reported that phloretin in a concentration of 1 mM reduced net D-glucose transport to 0.4 of the control value, which is qualitatively similar to what we have seen (Table 2).…”
Section: Discussionsupporting
confidence: 82%
See 2 more Smart Citations
“…However, given the small size of these vesicles, uptake measured at 15 sec would probably no longer be linear (Hopfer, 1978) so that uptake of D-glucose at the initial rate most likely exceeds that of L-glucose to a much greater extent. These same authors (Carstensen et al, 1977) reported that phloretin in a concentration of 1 mM reduced net D-glucose transport to 0.4 of the control value, which is qualitatively similar to what we have seen (Table 2).…”
Section: Discussionsupporting
confidence: 82%
“…Thus, Carstensen et al (1977) in a perfused preparation found D-glucose transport to be 2.4-2.7 times that of L-glucose, a value similar to what we have observed in the plasma membrane vesicle preparation (see Fig. 2).…”
Section: Discussionsupporting
confidence: 71%
See 1 more Smart Citation
“…This is probably due to a sharp fall in glucose supply resulting from urinary loss of glucose in the mother, and, to a lesser degree, in fetal urines. Furthermore, phloridzin could interfere with placental glucose transport since its aglycone, phloretin, decreases the transport of Z)-glucose in isolated guinea pig placenta (21) and in isolated human pla centa (5).…”
Section: Discussionmentioning
confidence: 99%
“…1), which is not transported specifically in the hemochorial placenta [Schröder et al, 1975;Carstensen et al, 1977Carstensen et al, , 1983. Therefore the transport of Lalanine is largely stereospecifically in the guinea pig placenta.…”
Section: Discussionmentioning
confidence: 97%